Treatment of dermatophytosis in elderly, children, and pregnant women - Subuhi Kaul; Savita Yadav; Sunil Dogra (Wolters Kluwer Medknow Publications, 2017)
Dermatophytic infection of the skin and its appendages is a common occurrence. Though usually straightforward, treatment of dermatophytosis becomes notably challenging in certain population groups - pregnant women, children, and elderly. Treatment with topical azoles/allylamines alone is effective in limited cutaneous disease in all three groups. Terbinafine is the preferred oral agent in elderly population for treatment of extensive cutaneous disease and onychomycosis due to its lack of cardiac complications and lower propensity for drug interactions. If required, additional physical/mechanical modalities can be employed for symptomatic onychomycosis. Data for systemic therapy in children mainly pertains to the treatment of tinea capitis. At present, very little data exists regarding the safety of systemic antifungals in pregnancy and there is an effort to restrict treatment to topical therapies because of their negligible systemic absorption.